Associations between depression and the incident risk of obesity in southwest China: A community population prospective cohort study - Liu, Tao; Wu, Bo; Yao, Yuntong; Chen, Yun; Zhou, Jie; Xu, Kelin; Wang, Na; Fu, Chaowei (Frontiers in Public Health, 2023)
Objective This study aimed to describe the incidence of obesity and investigate associations between depression and the risk of incident obesity among residents in Southwest China. Methods A 10-year prospective cohort study of 4,745 non-obese adults was conducted in Guizhou, southwest China from 2010 to 2020. Depression was assessed by the Patient Health Questionnaire-9 (PHQ-9) while the obesity was identified by waist circumference (WC) and/or body mass index (BMI). Cox proportional hazard models were used to estimate hazard ratios (HR), and 95% confidence intervals (CIs) of depression and incident obesity. Results A total of 1,115 incident obesity were identified over an average follow-up of 7.19 years, with an incidence of 32.66 per 1,000 PYs for any obesity, 31.14 per 1,000 PYs and 9.40 per 1,000 PYs for abdominal obesity and general obesity, respectively. After adjustment for potential confounding factors, risks of incident abdominal obesity for subjects with minimal (aHR: 1.22, 95% CI: 1.05, 1.43), and mild or more advanced depression (aHR: 1.27, 95% CI: 1.01, 1.62) were statistically higher than those not depressed, while there was no significant association with incident general obesity. The risks of any incident obesity among subjects with minimal (aHR: 1.21, 95% CI: 1.04, 1.40), mild or more advanced depression (aHR: 1.30, 95% CI: 1.03, 1.64) were significantly higher than those not depressed and positive association was found for PHQ score per SD increase (aHR: 1.07, 95%CI: 1.01, 1.13), too. The association was stronger significantly in Han Chinese (minimal: aHR: 1.27, 95% CI: 1.05, 1.52; mild or more advanced: aHR: 1.70, 95% CI: 1.30, 2.21) and farmers (minimal: aHR: 1.64, 95% CI: 1.35, 2.01; mild or more advanced: aHR: 1.82, 95% CI: 1.32, 2.51). Conclusion Depression increased the risk of incident obesity among adults in Southwest China, especially among Han Chinese and farmers. This finding suggests that preventing and controlling depression may benefit the control of incident obesity.